“Any news from Poland?” Representations of the Polish EU presidency in the Greek media - Serafeim, Katerina (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The purpose of the paper is to explore and analyze the news coverage of the first Polish presidency of the EU Council in the Greek media, as well as the role of the Greek media in the Greek citizens’ information process about issues regarding the Polish presidency and the promotion of European matters. Through a comparative quantitative and qualitative content analysis of the media, the paper aims to highlight the representations of the Polish EU presidency in the Greek media. In addition, the essay casts light on some crucial questions that arise: (1) How did the Polish EU presidency attract the Greek media’s attention? (2) What are the Greek media’s criteria for selection of EU-related events taking place in a foreign European country which are of great importance? (3) How many news items regarding the Polish EU presidency appeared on Greek TV, in newspapers and online media? (4) How frequently did representations of the term Poland, Polish EU presidency and Polish appear in Greek news items? (5) What was the Greek media’s attitude towards this foreign country? (6) How did the Greek media present the Polish EU presidency? As a host of numerous meetings and events or as an actor in charge, defining the major directions of the EU policy? (7) What was the attention given to Poland and to the Polish EU presidency in particular? (8) Within what spectrum did the Greek media comment on the role of the Polish EU presidency as chairman of the EU Council for 6 months?